Levando o direito a sério: uma exploração hermenêutica do protagonismo judicial no processo jurisdicional brasileiro - Motta, Francisco José Borges (Universidade do Vale do Rio do Sinos, 2009)
The reflections aligned in this work could be summarized in the following question: what does the Ronald Dwokin ́s theory of law, filtered by the Lenio Streck’s Hermeneutics Critical of Law, has to say about the (civil) court process which is practiced in Brazil? Dworkin has developed the concept, known by all, that there is, at the tables of a democratically constituted law, a “single correct answer” (the one right answer) for each one of the cases that reaches the forum. He was moved, from the beginning, by the purpose of identifying the rights (especially, the individual ones) that people really have at a democratic environment, and the understanding that the “court” should make these rights, as much as possible, accessible to their holders. Now, after dozens of years, in Brazil, comes Lenio Luiz Streck and says that those “right answers” are not only possible, but also necessary in Law. This research aims to better understand these messages (both Dworkin’s and Streck’s) and, with them, lead a discussion about the brazilian judicial process, which should be redefined from the need to provide the production of such “right answers” in Law. Working with “right answers in Law” means to recognize the strong degree of autonomy that Law has achieved, since the assumption of a non-authoritarian profile (neoconstitucionalism). Therefore, it implies, amongst other things, that Law is (far) more than what judges say it is. Good answers are the ones given by the Law, understood as integrity, not by the judge, individually considered. So that a hermeneutic understanding of Brazilian procedural law, committed to all these concepts, should be able to break the “dogma” of the judicial protagonism (movement that expands the powers and freedoms of the judge in the conduction and settlement of cases that come to the “court”). Therefore, in the hermeneutic paradigm, to take Law seriously is to dissolve the subjectivity of judging in the intersubjectivity that characterizes the Democratic State. In the midst of the process, taking Law seriously implies sharing the decision between the procedural actors, which should argue in favor of rights, and for the construction of the theory that best justifies, by principles, Law as a whole. The minimum that is required for this ideal to be achieved is to guarantee the procedure to be developed in effective contradictory, so that the parties' arguments are decisivefor the construction of the court’s decision (which should be confirmed, substantively, from the requirement of a “complete” reasoning of the judicial decision, covering not only the winning arguments, but also the reasons why the arguments in the opposite direction were rejected). At last, the final decision, in order to reflect a “correct answer”, should mirror a shared understanding amongst not only the procedural actors, but also between them and the judges from the past (successful juridical and institutional history).
Keywords: Garantia do contraditório; Hermenêutica jurídica; Princípios; Processo jurisdicional civil; Protagonismo judicial; Respostas corretas em direito; Civil court proceedings; Guarantee of the contradictory; Judicial protagonism; Juridical hermeneutics; Principles; Correct answers in law; Ciências Sociais Aplicadas